1969
DOI: 10.1002/pssb.19690360120
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of FeCr2S4 and CoCr2S4

Abstract: S e w measurements of magnetic properties of pure FeCr,S, and CoCr2S, have been carried out. The g-factors of cobalt, iron, and chromium in these compounds were evaluated. Exchange interactions were deduced from computation of the experimental paramagnetic and magnetization curves. De nouvelles mesures des propriiftifs magnktiques ont iftif effectukes sur les coniposirs FeCr,S, et CoCr,S, obtenus A 1'6tat pur. Les facteurs g du cobalt, fer et chrome dans ces composes ont At8 irvaluifs. Le calcul des courbes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0
4

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 13 publications
7
16
0
4
Order By: Relevance
“…Then (B -A) may become negative but small magnitude because of the cancellation of B and A. On the other hand, ferrimagnetic and ferromagnetic crystals with a low T, has a rather large antiferromagnetic part or large K i k (Baltzer et al, 1966; Gibart et al, 1969;Stapele, 1982;Kanomata et al, 1985). Therefore, a large value of B is expected.…”
Section: 1b Frequency Shgt Below Tmentioning
confidence: 94%
See 1 more Smart Citation
“…Then (B -A) may become negative but small magnitude because of the cancellation of B and A. On the other hand, ferrimagnetic and ferromagnetic crystals with a low T, has a rather large antiferromagnetic part or large K i k (Baltzer et al, 1966; Gibart et al, 1969;Stapele, 1982;Kanomata et al, 1985). Therefore, a large value of B is expected.…”
Section: 1b Frequency Shgt Below Tmentioning
confidence: 94%
“…These modes exhibit relatively large shifts below T, in comparison with those of the A-and B-modes, which are seen in Figures 2 and 3. This has been explained by the large magnitude of B in Eq (8) in comparison with that of A, which was predicted from the large pressure dependence of Kik estimated from the Curie temperature (Gibart, Dormann and Pellerin, 1969;Srivastava, 1969;Kanomata, Shirakawa and Kaneko, 1985;Sakai and Pifer, 1986). Since the Cd or Fe ions contribute strongly to Kik (Baltzer et al, 1966) and also to the C-and D-modes (Bruesch et al, 1972;Wakamura, Arai, Onari, Kudo and Takahashi, 1973), a large value of (B -A) is expected on the modes.…”
Section: 1b Frequency Shgt Below Tmentioning
confidence: 94%
“…1 [39]. The successful refinement of the FeCr 2 S 4 magnetic structure indicated that the spin-only moments are reduced from expected values of −4.2 µ B for Fe 2+ with S = 2 and g = 2.1 and 3.0 µ B for Cr 3+ with spin S = 3/2 and g = 2.…”
mentioning
confidence: 90%
“…An important difference between y and T c values could be attributed to a non defined ferromagnetic transition. However, sample with x ¼ 0:2 showed a ferrimagnetic behavior for Tp120 K. The high temperature data was fitted by using the well known relation [4,5]: 1=w ¼ T=C þ 1=w 0 À s=ðT À y f Þ with the parameters: 1/w 0 =1054.5 (3) g/emu; C=7.6 (emu K/g); y f =119 K; s ¼ 3862:7(7) (K g/emu).…”
Section: Resultsmentioning
confidence: 99%